2009
DOI: 10.3168/jds.2009-2018
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body glucose metabolism and mammary energetic nutrient metabolism in lactating dairy cows receiving digestive infusions of casein and propionic acid

Abstract: This study analyzed the effect of propionate (C3) and casein (CN) on whole-body and mammary metabolism of energetic nutrients. Three multiparous Holstein cows fitted with both duodenal and ruminal cannulas were used in 2 replicated Youden squares with 14-d periods. Effects of CN (743 g/d in the duodenum) and C3 (1,042 g/d in the rumen) infusions, either separately or in combination as supplements to a grass silage diet, were tested in a factorial arrangement. The control diet provided 97% of energy and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 44 publications
8
62
4
1
Order By: Relevance
“…Proteins seem to stimulate the de novo FA synthesis, as suggested by the increase in the percentages of SCFA and MCFA (and the consecutive decrease in LCFA percentages). This increase in SCFA and MCFA could be linked to an increase in arterial concentrations or extraction rates of some mammary FA synthesis precursors (C2 and non-esterified FA: Guinard et al, 1994;b-hydroxybutyrate: Vanhatalo et al, 2003;Lemosquet et al, 2009b). The hypothesis of dietary protein stimulating lipomobilization is not consistent with the observed decrease in LCFA percentages.…”
Section: Discussioncontrasting
confidence: 46%
“…Proteins seem to stimulate the de novo FA synthesis, as suggested by the increase in the percentages of SCFA and MCFA (and the consecutive decrease in LCFA percentages). This increase in SCFA and MCFA could be linked to an increase in arterial concentrations or extraction rates of some mammary FA synthesis precursors (C2 and non-esterified FA: Guinard et al, 1994;b-hydroxybutyrate: Vanhatalo et al, 2003;Lemosquet et al, 2009b). The hypothesis of dietary protein stimulating lipomobilization is not consistent with the observed decrease in LCFA percentages.…”
Section: Discussioncontrasting
confidence: 46%
“…The most noticeable is glucose, the precursor of lactose, which is the primary osmotic regulator of milk volume (Lemosquet et al, 2009b;Wall and McFadden, 2012). In the present study, higher level of supplied energy resulted in higher milk yield and lactose content.…”
Section: Discussionmentioning
confidence: 44%
“…Effects of glucose status on glucose carbon return might involve C3 return from mammary pentose phosphate cycle as this pathway is of importance for NADPH generation for de novo fatty acid synthesis in the mammary gland. Lemosquet et al (50) showed that mammary release of L-lactate was changed to mammary uptake with exogenous supply of glucogenic substrate (propionate and nonessential amino acids). Lactate release by skeletal muscle might as well contribute to the return of glucose carbon to the liver, whereas the PDV release of L-lactate seems primarily related to feed intake (29; Raun and Kristensen, unpublished data).…”
Section: Availability and Partitioning Of Glucogenic Precursorsmentioning
confidence: 99%